Corporate governance and Islamic social reporting: Indonesia Islamic banking development roadmap era - Dosinta, Nina Febriana; Yunita, Khristina (Journal of Contemporary Accounting, 2024)
This research examines the corporate governance effect on Islamic Social Reporting (ISR). This research was conducted in 2015-2022, used the ISR codification, collected from the annual reports of ten Indonesian Islamic banks, and applied the Stakeholder Theory approach which has never been done previously. The research results show that Board of Commissioners’ meetings, Audit Committee meetings, and Sharia Supervisory Board meetings significantly and positively affect ISR. These findings imply that supervision through the meetings of the Board of Commissioners, Audit Committees, and Sharia Supervisory Board plays a role in detecting ISR. Corporate governance in Islamic banks continuously seeks to maintain sustainability in Islamic banks, including the support for stakeholders. ISR is a form of Islamic bank accountability to show that Islamic banks always prioritize their stakeholders, including the support for the Indonesia Islamic banking development roadmap prepared by the Financial Services Authority.